2007
DOI: 10.1007/s10494-007-9080-8
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy Simulation of Film Cooling Flows with Variable Density Jets

Abstract: The present paper investigates the impact of the velocity and density ratio on the turbulent mixing process in gas turbine blade film cooling. A cooling fluid is injected from an inclined pipe at α=30 • into a turbulent boundary layer profile at a freestream Reynolds number of Re ∞ = 400,000. This jet-in-a-crossflow (JICF) problem is investigated using large-eddy simulations (LES). The governing equations comprise the Navier-Stokes equations plus additional transport equations for several species to simulate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This might come from the difference of vortex structure after the cooling hole exit, that should be strongly influenced by the turbulence level around the cooling hole. [19] x/d ) 0.5 /U m . Since turbulence was not imposed at the inlet of the main stream region in the DES simulation, the distribution of TL is much different from the one measured by Pietrzyk et al [24].…”
Section: Film Cooling Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…This might come from the difference of vortex structure after the cooling hole exit, that should be strongly influenced by the turbulence level around the cooling hole. [19] x/d ) 0.5 /U m . Since turbulence was not imposed at the inlet of the main stream region in the DES simulation, the distribution of TL is much different from the one measured by Pietrzyk et al [24].…”
Section: Film Cooling Effectivenessmentioning
confidence: 99%
“…10. The results of previous experiments [15][16][17] and LES simulations [3,9,19] are also plotted in the figure. The LES results agree well with the experiments.…”
Section: Film Cooling Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuller and Walters (1991), Williams and Hartfield (1996) and Wang (2000) used different inclination angle such as 25, 35, 45 and 60 revealing the velocity and vorticity fields. Most of reported studies on inclined jets dealt with the effects of inclination angle on the flow structure associated with film cooling phenomena such as Rowbury et al (2001), Bayraktar and Yilmaz (2008), Renze et al (2008) and Bayraktar and Yilmaz (2011).…”
Section: Fig 1 Dominant Vortex Structures In Jicfmentioning
confidence: 99%
“…The results showed that the higher values of VR have a strong impact on Downloaded by [New York University] at 22:46 23 June 2015 the cooling performance because it causes a stronger penetration of the jet in cross-flow, resulting in large streamwise vortices downstream of the jet exit and entrains the cross-flow partially into this zone. Later, the impact of density and VRs was investigated by Renze et al [12] using LES. Gases of different densities were injected from an inclined pipe at 30 • into an airstream at a freestream Reynolds number of 400,000 and different values of VR of 0.1, 0.28, and 0.48.…”
Section: Introductionmentioning
confidence: 99%